Staffing Processes on Workers’ Retention in Federal Polytechnic Ede, Osun State, Nigeria - Oyelekan I. Ayantunji; Zacchaeus O. Olonade; Shadare O. Adetunji; Omotoye O. Oluwatobi (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The study investigates the influence of staffing processes on workers’ retention at the Federal Polytechnic in Ede, Osun State. The study was a survey that employed a descriptive design. Its target population comprises all employees who have spent at least three years at the Federal Polytechnic in Ede, Osun State. A total of 140 respondents were selected for the study using a proportionate stratified random sampling method. A questionnaire format was used to obtain the relevant data. Out of 140 copies of the questionnaires, 127 copies were returned and utilised for the study. The collected data was analysed using Regression Analysis, Pearson Moment Correlation with the aid of the Statistical Package for Social Sciences (SPSS) version 25.0. The findings show that the staffing process (recruitment and selection) significantly influenced workers’ retention at the Federal Polytechnic, Ede. Based on the study’s findings, it was concluded that the staffing process (recruitment and selection practices) significantly influenced employee retention at the Federal Polytechnic in Ede, Osun State. It was recommended that all applicants be given equal opportunities; favourites and other such things should be avoided while providing a level playing field.